Nigeria - Targeting Communities for Effective Poverty Alleviation - World Bank (Washington, DC, 2012)
An important finding from analyzing the survey data from the poverty assessment study on Nigeria is the concentration of the poor in communities in which most of the other households are also poor, and the tendency of the non-poor households to reside in communities in which the population is largely non-poor. As a result, the overall income inequality in the country is due largely to income inequality between communities and much less to income inequality between households within communities. To illustrate this concentration of the poor and the non-poor in separate communities, all the communities that were included in the household expenditure survey were divided into four categories according to two criteria: first, the share of poor households in the community and second, the average per capita income of all the households in the community. Although the sample for each community is very small, all the conclusions have been drawn for the entire category of communities in which the size of the sample was adequate.